Heavy metal content in agricultural soil from the Ariari region in the Meta department (Orinoquia, 2015)
Using technologies focused on agricultural systems' increased performance/yield has led to various environmental issues, including pesticide and fertiliser use since these are potential sources of heavy metals. This research was aimed at determining the concentration of heavy metals (i.e. Cu, Zn, Ni, Pb, Cd, Cr) in highly weathered tropical soils (oxisol) subjected to intensive agricultural use over a period of time lasting more than 10 years in the Ariari region. The following sequence gives the concentration of the metals so obtained: Zn > Cu > Pb > Cr > Ni; in no case did this exceed the maximum permissible limits set by the United States' Environmental Protection Agency (EPA). Likewise, it is likely that the heavy metals are mobilising in the soil-plant matrix, according to the physicochemical parameters.Key words: Soil contamination; agricultural supplies; heavy metal; agricultural soil.
Keywords: Soil contamination; agricultural supplies; heavy metal; agricultural soil